(3QSGdI GdQhV Ydi CfSGH GdMhVs - (3SjO YHO Gddg Hf GdMGL EHQGgje GdYdhj,J (B1233 (3g` s ((3ehQjJGfjG s)
(3ChdgG (B:s
(3CeG HYO abO UM hKHJ eG cJH Cgd GdJGQjN Cf CfSGH Cgd GdMhV cdge eG Hjf TQja EOQjS hMSGfi gGTei aCbhd hHGddg GdJhajb hdGMhd hdGbhI EdG HGddg GdYdi GdYXje s
(3BNQgG (B:s
(3hGfJgJ GdQSGdI GdeSeGg HQSGdI GdQhV Ydi CfSGH Cgd GdMhV Ydi jO eDda ef HYV cJH GdJhGQjN hGdCfGSH hef HYV GdQhGjJ GdUMjMGJ hGddg CYde hgh Gdehab ddQTO hGdUGH hEdjg GdeQLY hGdeBH s
(3GdfSNI HgG MhGTs
(3fSNI MOjKI YdjgG bQGAI hJUMjMGJs
(3hcJHJ ai YUQ GdeDda Ydi jO CMO JdGejPg s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJGQjNs